Harvesting Plant and Microbial Biodiversity for Sustainably Enhanced Food Security - Francesca Sparvoli (Frontiers Research Topics, 2018)
The World population will reach 9 billion by 2050, with the majority of this growth occurring in developing countries. On the other hand, one in nine of the World's population suffers from chronic hunger, the vast majority of which live in developing countries. We therefore need to find new and sustainable solutions to feed this increasing population and alleviate the predicted negative impact of global changes on crop production. This e-Book deals with new strategies to improve food security and livelihoods in rural communities, reduce vulnerability, increase resilience and mitigate lthe impact of climate change and land degradation on agriculture. This collection of 18 articles addresses the major abiotic factors limiting crop production worldwide, how to characterize and exploit the available plant biodiversity to increase production and sustainability in agrosystems, and the use of beneficial microbes to improve production and reduce the use of fertilizers and pesticides.